Dissociative recombination measurements of SH+ with cold electrons. (August 2015) - Becker, A; Domesle, C; Geppert, W D; Grieser, M; Krantz, C; Repnow, R; Savin, D W; Schwalm, D; Wolf, A; Yang, B; Novotný, O
Synopsis: We have experimentally investigated dissociative recombination of SH + with low-energy electrons. The merged-beams rate coefficient was measured at the TSR ion storage ring in Heidelberg, Germany. From these data the cross section was extracted and used to generate a plasma rate coefficient for plasma temperatures down to 10 K, which are relevant for astrochemical models. Furthermore, we have determined branching ratios of product excitation states utilizing a novel analysis method for imaging data.